Coastal habitat and biological community response to dam removal on the Elwha River. Issue 4 (5th September 2017) - Foley, Melissa M.; Warrick, Jonathan A.; Ritchie, Andrew; Stevens, Andrew W.; Shafroth, Patrick B.; Duda, Jeffrey J.; Beirne, Matthew M.; Paradis, Rebecca; Gelfenbaum, Guy; McCoy, Randall; Cubley, Erin S.
Abstract: Habitat diversity and heterogeneity play a fundamental role in structuring ecological communities. Dam emplacement and removal can fundamentally alter habitat characteristics, which, in turn, can affect associated biological communities. Beginning in the early 1900s, the Elwha and Glines Canyon dams in Washington, USA, withheld an estimated 30 million Mg of sediment from river, coastal, and nearshore habitats. During the staged removal of these dams, the largest dam removal project in history, over 14 million Mg of sediment were released from the former reservoirs. Our interdisciplinary study in coastal habitats, the first of its kind, shows how the physical changes to the river delta and estuary habitats during dam removal were linked to responses in biological communities. Sediment released during dam removal resulted in over a meter of sedimentation in the estuary and over 400 m of expansion of the river mouth delta landform. These changes increased the amount of supratidal and intertidal habitat, but also reduced the influx of seawater into the pre‐removal estuary complex. The effects of these geomorphic and hydrologic changes cascaded to biological systems, reducing the abundance of macroinvertebrates and fish in the estuary and shifting community composition from brackish to freshwater‐dominated species. Vegetation did not significantly change on the delta, but pioneer vegetation increased during dam removal, coinciding with the addition of newly available habitat. Understanding how coastal habitats respond to large‐scale human stressors, and in some cases the removal of those stressors, is increasingly important as human uses and restoration activities increase in these habitats.